MANFAAT TEKNIK REBOZO TERHADAP KEMAJUAN PERSALINAN - Durrotun Munafiah; Lestari Puji Astuti; Mike Mitrasari Parada; Maria Rosa Mictica Demu (Midwifery Care Journal, 2020)
The birth process is to help and encourage safe and healthy births for mothers and babies, so that the roles and responsibilities of health workers are needed to anticipate and overcome the complications that occur in labor. Prolong labor is one of the factors that influence maternal mortality. The result of the Survey on 2015 is Maternal Mortality Rate (MMR) is 305 per 100,000 live births in Indonesia. The rebozo technique is a non-pharmacological method that makes the muscles of the pelvis more relaxed and gives the pelvic space more space and  open so that it helps accelerate the opening of the cervix and help descending of the fetal head, so that can help shorten the time of delivery. The aim of the study was determined the differences in the effectiveness of the rebozo technique on cervical dilatation and descend of the fetal head in active phase of first stage in labor mothers. Methodology of this study was Quasy experimental design. It take pre-post test on one group design. Population and sample were 20 primigravidas mothers in active phase of the first stage of labor. Sampling technique used accidental sampling. The result of this study that there was effectiveness of rebozo technique on opening of the cervix during the active phase with p-value 0.012. Conclusion is there was an effectiveness of the rebozo technique for descending of fetal head in the active phase of the first stage of maternal delivery with p-value 0.028